An Autonomous Approach for Type Categorization of Product Data Based on Numerous Text and Attribute Factorizations - Baruah, Sudesna; Lakshmi V., Bagya; Devaraj, Navneeth; A., Gnanaprakash; Jayaram, Deepak Kumar (Indian Journal of Computer Science, 2022)
Product categorization or Product classification is an area of Natural Language Processing. This special area happens to have a lot of challenges, especially for e-commerce organizations. Scientists and researchers have actively worked on this area over the years using various machine learning & artificial intelligence techniques. Product categorization is the placement and organization of products into their respective categories.